A dynamic model of settlement - Thorsten Volker Koeppl; Cyril Monnet; Ted Temzelides (European Central Bank (ECB), 2006)
We investigate the role of settlement in a dynamic model of a payment system where the ability of participants to perform certain welfare-improving transactions is subject to random and unobservable shocks. In the absence of settlement, the full information first-best allocation cannot be supported due to incentive constraints. In contrast, this allocation is supportable if settlement is introduced. This, however, requires that settlement takes place with a sufficiently high frequency.
Keywords: E4; E5; 330; Intertemporal Incentives; payments; settlement; Zahlungsverkehr; Intertemporale Allokation; Anreiz; Theorie